Recurrent Laryngeal Nerve Invasion by Thyroid Cancer: Laryngeal Function and Survival Outcomes. (1st April 2022) - Brooks, Jennifer A.; Abdelhamid Ahmed, Amr H.; Al‐Qurayshi, Zaid; Kamani, Dipti; Kyriazidis, Natalia; Hammon, Rebecca Jean; Ma, Hongzhi; Sritharan, Niranjan; Wasserman, Isaac; Trinh, Lily N.; Iwata, Ayaka J.; Saito, Yoshiyuki; et al.
Abstract : Background: Recurrent laryngeal nerve (RLN) invasion by thyroid carcinoma represents an advanced disease status with potentially significant co‐morbidity. Methods: In a retrospective single‐center study, we included patients with invaded RLNs operated on while using nerve monitoring techniques. We studied pre‐, intra‐, and postoperative parameters associated with postoperative vocal cord paralysis (VCP); 5‐year recurrence‐free survival (RFS); and 5‐year overall survival (OS) in addition to two subgroup analyses of postoperative VCP in patients without preoperative VCP and based on source of RLN invasion. Results: Of 65 patients with 66 nerves‐at‐risk, 39.3% reported preoperative voice complaints. Preoperative VCP was documented in 43.5%. The RLN was invaded by primary tumor in 59.3% and nodal metastasis in 30.5%. Papillary thyroid carcinoma was the most common pathologic subtype (80%). After 6 months, 81.8% had VCP. Complete tumor resection of the RLN was not associated with 5‐year RFS ( p  = 0.24) or 5‐year OS ( p  = 0.9). Resecting the RLN did not offer statistically significant benefit on 5‐year RFS ( p  = 0.5) or 5‐year OS ( p  = 0.38). Radioactive Iodine (RAI) administration was associated with improvement in 5‐year RFS ( p  = 0.006) and 5‐year OS ( p  = 0.004). Patients without preoperative VCP had higher IONM amplitude compared with patients with VCP. After a mean follow‐up of 65.8 months, 35.9% of patients had distant metastases, whereas 36.4% had recurrence. Conclusion: Preoperative VCP accompanies less than half of patients with RLN invasion. Invaded RLNs may have existent electrophysiologic stimulability. Complete tumor resection and RLN resection were not associated with better 5‐year RFS or OS, but postoperative RAI was. Level of Evidence: 4 Laryngoscope, 132:2285–2292, 2022